2008
DOI: 10.1002/em.20410
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐specific metabolic activation and mutagenicity of 3‐nitrobenzanthrone in Muta™Mouse

Abstract: 3-Nitrobenzanthrone (3-NBA) is a mutagen and suspected human carcinogen detected in diesel exhaust, airborne particulate matter, and urban soil. We investigated the tissue specific mutagenicity of 3-NBA at the lacZ locus of transgenic MutaMouse following acute single dose or 28-day repeated-dose oral administration. In the acute high dose (50 mg/kg) exposure, increased lacZ mutant frequency was observed in bone marrow and colonic epithelium, but not in liver and bladder. In the repeated-dose study, a dose-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…The present study investigated the empirical relationship between total DNA adduct levels in selected tissues observed 18 h following a single oral administration of 25, 50 or 75 mg/kg 3-NBA, and total MF in the same tissues 18 h (bone marrow, small intestine), 3 days (bone marrow, liver, small intestine, colon) or 28 days (bone marrow, liver, small intestine, colon, lung) after treatment. The in vivo RAL results observed at 18 h after a single acute dose are new data, while the MF data include new data, as well as those previously published (37,48). In addition, investigation of the MF-RAL relationship in the present study incorporates published data on RAL and MF in FE1 cells following in vitro exposure to 0.1, 1, 3 and 10 µg/ml (37).…”
Section: Resultsmentioning
confidence: 59%
See 4 more Smart Citations
“…The present study investigated the empirical relationship between total DNA adduct levels in selected tissues observed 18 h following a single oral administration of 25, 50 or 75 mg/kg 3-NBA, and total MF in the same tissues 18 h (bone marrow, small intestine), 3 days (bone marrow, liver, small intestine, colon) or 28 days (bone marrow, liver, small intestine, colon, lung) after treatment. The in vivo RAL results observed at 18 h after a single acute dose are new data, while the MF data include new data, as well as those previously published (37,48). In addition, investigation of the MF-RAL relationship in the present study incorporates published data on RAL and MF in FE1 cells following in vitro exposure to 0.1, 1, 3 and 10 µg/ml (37).…”
Section: Resultsmentioning
confidence: 59%
“…Similarly, in another study, we also showed that a 28-day repeated dose oral exposure of 2 or 5 mg/kg, followed by a 28-day sampling time, induced a significant increase in MF in bone marrow and liver (37), but showed no significant increase in MF in lung and intestinal epithelium at any dose. Both studies (i.e., (37,48)) also showed a significant increase in MF in Muta™Mouse FE1 cells exposed to 3-NBA in vitro (0.1, 1, 3 and 10 µg/ml).…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations